A Retrospective Study: Trichomoniasis - Miranti, Umi; Murtiastutik, Dwi (Faculty Of Medicine Airlangga University, 2014)
Background: Trichomoniasis is sexually transmitted infection caused by Trichomonas vaginalis. It caused urethritis on male and vaginitis on female. Purpose: To find out the general description of new patient of Trichomoniasis in Sexually Transmitted Infection Division, Departement of Dermato-veneorology of Dr. Soetomo General Hospital Surabaya from Januari 2008 to December 2012. Methods: Retrospective study method was performed by evaluating medical record of Trichomoniasis patient including the patients visitation, age, gender, marital status, occupation, patients complain, periode of illness, coitus suspectus, sexual partner, the history of previous treatment, the description of genital discharge, laboratory examination, management, and follow up. Results: There were 31 patients with Trichomoniasis. The majority of age was 25-44 years old. The most complained is itching genital discharge, and the most characteristic is purulent. Trichomonas vaginalis was found in all patients on wet preparation. 12 patients did not return to the hospital anymore. Conclusions: Based on 5 years data in medical record, most of patient complained about itchy genital discharge, and the most characteristic is purulent. In all patients found Trichomonas vaginalis in wet preparation and the main therapy of trichomoniasis is metronidazole.Key words: trichomoniasis, sexually transmitted infection, retrospective study.